Effect of water flow on growth of Catla catla (Hamilton, 1822) reared in recirculatory aquaculture system - Nagar, Pankaj; Mishra, Ashutosh; Kumar, Prem; Tewari, Hema; Ram, R. N. (Indian Journal of Fisheries, 2019)
Production performance of  the Indian major carp, catla Catla catla  (Hamilton, 1822) was examined at different water flow rates in recirculatory aquaculture system (RAS), in Tarai region of Uttarakhand. The experiment was conducted in 12 FRP tanks of RAS  with sand filter and UV filters, with  four treatments and three replicates for each treatment viz., control, T0 (83 l h-1 or one time in two days); T1 (667 l h-1 or 4 times in a day); T2 (333 l h-1 or 2 times in a day) and T3 (167 l h-1 one time in a day) from November 2015 to April 2016. The fingerlings of catla   having uniform body weight (10.00±0.6 g) were stocked randomly in all treatment groups at the rate of 25 no.m-3. Physical properties of water such as water temperature, electrical conductivity and total dissolved solids were analysed weekly throughout the experimental period and ranged from 15.8 to 27.8°C, 271 to 384.3 µS cm-1 and 216.3 to 274 mg l-l, respectively.  Water parameters  such as pH, dissolve oxygen, free carbon dioxide, alkalinity, hardness, ammonia, nitrate and phosphate were also analysed which varied from 7.2 to 8.4, 5.4 to 7.9 mg l-l, 1.8 to 3 mg l-l, 118 to 167.3 mg l-l, 133.3 to 241.6 mg l-l, 0.02 to 0.08 mg l-l, 0.11 to 0.42 mg l-l and 0.02 to 0.08 mg l-l respectively. The best food conversion ratio (FCR) was recorded in T0 (1.61) followed by T3 (1.65), T1 (1.70) and T2 (1.81). Highest specific growth rate (SGR) was recorded in T2 (0.88%), followed by T1 (0.86%), T3 (0.85%) and T0 (0.84%). The best protein efficiency ratio (PER) was recorded in T2 (2.31) followed by T3 (2.54), T1 (2.56) and T0 (2.62). Among different treatment groups, the survival rate of  catla varied from 78 in T0 to 83%  in T1.. Significantly higher (p